Reverse shoulder joint replacement in rheumatoid arthritis: medium-term results in 37 patients - M. A. Makarov; A. A. Roskidailo; M. V. Panteleev (Современная ревматология, 2018)
Objective: to assess functional results and quality of life in patients with rheumatoid arthritis (RA) after reverse shoulder joint replacement.Patients and methods. Examinations were made in 37 patients with RA involving the shoulder joint, who underwent shoulder joint replacement using a reverse DeltaX-tend DePuy prosthesis in 2006–2017. The investigators studied the volume of movements, the level of pain using the visual analogue scale, the function of the shoulder joint using the American Shoulder and Elbow Surgeons (ASES) Shoulder Score and the upper limb as a whole by the Disability of the Arm, Shoulder and Hand (DASH) questionnaire, a patient's functional status by the Health Assessment Questionnaire (HAQ), quality of life (QL) by EQ-5D (Euro Quolish instrument) and analyzed shoulder X-ray films before and in the late periods after surgery.Results. The volume of shoulder joint movements was found to increase. At 28.7 months postsurgery, the mean volume of flexion, abduction, and external rotation was 107.4Ѓ}15.2, 128.3Ѓ}8.5, and 46.4Ѓ}5.5°; respectively (p≤0.05). The patients experienced no pain in the late periods following surgery. Prior to surgery and at control examination, the mean ASES scores were 25.0Ѓ}4.7 and 79.4Ѓ}6.4, respectively (p≤0.05). Before surgery, the mean DASH score was 63.8Ѓ}4.2; in the late periods it decreased to 18.2Ѓ}8.6 (p ≤ 0.05). The mean preoperative HAQ score was 2.81; following surgery, it also decreased to 1.39 (p≤0.05). The postoperative EQ-5D QOL index score increased from 0.41 to 0.72. The rate of complications reached 10.8%.Conclusion. Reverse endoprosthetic replacement for end-stage shoulder joint damage (Larsen 4–5) with rotator cuff defect makes it possible to increase the volume of movements, to reduce pain, and to improve upper limb function, functional status, and quality of life in patients with RA.